Teacher's leadership in learning processes at kindergartens - Niron, Maria Dominika; Suyata, Suyata; Suardiman, Siti Partini (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2017)
The aim of this study was to find out the effective kindergarten teacher's behaviour in influencing, mobilizing, and developing students in teaching learning process. This research was phenomenological qualitative research. The main instruments of this research were the researcher and observation manual. The focus of this research was the way teachers teach in the learning process in group A of Indriyasana Kindergarten, Indriarini Kindergarten, and ABA Pokoh Kindergarten. The data validity of this research was tested by using repeated observation, resource triangulation, and technique triangulation. The componential data was analyzed by employing inductive technique from Spradley's qualitative model and Miles and Huberman analysis model. The result of the research showed that teacher's effective ways to influence, mobilize, and develop students in teaching learning process are as follows: 1. Reciting yell, clap yell, and asking students to sing. The content of yell, clap yell, and song was appropriate with values which were developed based on vision, mission, and the goal of Kindergarten institution. Yells, clap yell, and song were democratic and they were the form of the value of learning leadership. 2. In some situations, there was a tendency where the teacher used more autocratic way to influence, mobilize, and develop students in learning process such as the verbal way in which teacher call students' name and non-verbal way in which teacher put his index finger on his lip as a sign to ask students to be quiet. The other non-verbal ways were: shaking head as a sign of disagreement, raising thumb as a sign of reinforcement, and nodding as a sign of agreement. Sometimes, teachers also used laissez-fair methods such as neglecting students/letting students behave as they want. Keywords: leadership, teacher's leadership behaviour, learning process in Kindergarten